Husbandry of a pink fairy armadillo (Chlamyphorus truncatus): Case study of a cryptic and little known species in captivity - Superina, Mariella (2011)
Pink fairy armadillos, Chlamyphorus truncatus, are poorly known fossorial mammals that are endemic to central Argentina. These smallest of all extant armadillos are rarely observed in the field and extremely difficult to maintain under captive conditions. This case study describes the husbandry of a male pink fairy armadillo that was maintained in an artificial environment for 8 months. A stable, undisturbed environment consisting of abundant compact sand and hiding places on the surface was the key to its successful maintenance. The artificial diet consisted of a semiliquid mixture of ground cat food, insectivore diet, mashed banana, vitamins, and minerals. Any slight modification to its environment or diet triggered a stress response.